COMPARATIVE CHARACTERISTICS OF MORPHOLOGICAL INDICES OF THE STOMACH IN EXPERIMENTAL LIVER DAMAGE - Sanoyev Farhod Fayzulloyevich (TADQIQOTLAR, 2025)
Annotation: Numerous fundamental studies devoted to the problem of the complex influence of exogenous and endogenous effects on the human body have proven their depressive effect on the body’s regulatory systems. At the same time, the study of morphological indices of gastric tissue, sensitive to homeostasis disturbances in experimental conditions with liver damage, remains relevant for researchers.